We the nation: the lost decades - "Palkhivala, Nani A." (New Delhi, 1994)
A book for all persons and all seasons indeed. Each topic is illuminated with sensitivity and sunlight-clear exposition. Public memories are irresponsibly short and selective, and this book, spanning as it does the panorama of the last ten tumultuous years, becomes essential reading - the history that must be1 read so that we are not condemned to repeating it. India, the sleeping giant of an economy in the words of Lee Kuan Yew is, at last, slowly stirring from its long night of slumber, drugged as it has been for decades with the opiate of socialism. This amazing subcontinent with its mosaic of colours, cultures, contrasts and maddening contradictions, always has, thanks to vast quantities of its own indigenously manufactured red tape and venal politicians, been held in thrall for so long. It is only now, and that too hesitantly, that India is moving to take its rightful place in the community of nations of the world. What ails India, what its potential is, how magnificent its heritage is, how richly endowed it is by both history and nature, are all highlighted in this book.
Keywords: Indiaa-Politics and government